EFEKTIVITAS PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY (AR) PADA MATERI ALJABAR TERHADAP HASIL BELAJAR SISWA SMP - Siti Nur Ambarwati; Khafidhoh Nurul Aini; Arezqi Tunggal Asmana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Algebra learning at the junior high school level remains challenging due to the abstract nature of algebraic concepts, causing students difficulties in understanding variables, symbols, and algebraic operations. This study aims to develop and examine the effectiveness of an Augmented Reality (AR)-based learning media for Algebra material in improving junior high school students’ learning outcomes. This research employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The developed product was an Android-based application called Belajar Aljabar, which integrates AR visualization, learning materials, exercises, and interactive quizzes. The research subjects were seventh-grade students at MTs Al Islamiyyah Mojoasem. Data were collected through expert validation, pretest-posttest assessments, and student response questionnaires. The results showed that the developed media was categorized as highly valid based on material and media expert validation, with an average score of 3.64. The implementation results indicated an improvement in students’ learning outcomes, with the average score increasing from 60.50 in the pretest to 88.50 in the posttest, and an N-Gain score of 0.71 categorized as high. The Paired Sample t-Test results showed a significance value of 0.000 (<0.05), indicating a significant difference after using the media. Student responses reached 91.88% in the very good category. Therefore, the AR-based learning media developed in this study is valid and effective as an alternative Algebra learning medium to improve students’ conceptual understanding and learning outcomes.